The Effects of an Online Theory-Based Bone Health Program for Older Adults. (September 2017) - Nahm, Eun-Shim; Resnick, Barbara; Brown, Clayton; Zhu, Shijun; Magaziner, Jay; Bellantoni, Michele; Brennan, Patricia Flatley; Charters, Kathleen; Brown, Jeanine; Rietschel, Mathew; An, Minjeong; Park, Bu Kyung
An estimated 10 million Americans age 50 and older have osteoporosis, and many experience associated fractures. Although several interventions have been shown to be effective in preventing osteoporosis, their impact on bone health among older adults was limited. The aim of this study was, therefore, to examine the effects of a theory-based online bone health program (Bone Power program) for a large number of older adults. The 8-week program included learning modules, discussion boards, and other resources. Participants ( N = 866; M age = 62.5 years) were recruited online and randomized into a Bone Power or control group. At the end of the intervention, the Bone Power group showed significantly greater improvement over the control group in osteoporosis knowledge, self-efficacy/outcome expectations for calcium intake and exercise, and calcium intake and exercise behaviors. This study's findings suggest that online health programs can be effective in improving older adults' knowledge, beliefs, and health behaviors.